The Study of Serum Vitamin D Level In Patient With Pulmonary Hypertension And Right Ventricular Systolic Dysfunction Detected by Transthoracic Echocardiography (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Objective: To aim the vitamin D level in patient with pulmonary hypertension and right ventricular systolic dysfunction. Patients and methods: This case-control study was conducted on twenty five patients with pulmonary hypertension who were admitted to Merjan Teaching Hospital in Al- Hilla, Babylon-Iraq, during the period from June to December 2016. There were 13 males and 12 females among the patients; ages of them ranged from 39 to 80 years with a mean age of 59.50±11.881 years. The controls were equal in number to the patients and were relatives of them; they were healthy with respect to any cardiac or pulmonary morbidity; and were matched by age and gender. Blood samples were collected from both groups  to estimate the level of vitamin D and transthoracic echocardiographic studies were done for them to evaluate right ventricular systolic pressure (RVSP) and tricuspid annular plane systolic excursion (TAPSE) to assess right ventricular systolic function. Results: The study results demonstrated that there was a statistically significant dif- ference between patients and controls regarding vitamin D level, right ventricular systolic pressure (RVSP) and tricuspid annular plane systolic excursion (TAPSE) . Conclusion: Vitamin D deficiency is more frequent and prevalent among patients with Pulmonary hypertension and right ventricular systolic dysfunction compared to con- trol group of subjects. Future large scale studies are therefore warranted to validate benefit of supplementing vitamin D in patients at risk for pulmonary hypertension who are likely to be vitamin D deficient.